UPAYA GURU BK MENINGKATKAN DISIPLIN PESERTA DIDIK MELALUI LAYANAN KONSELING PERORANGAN DI SMA PERTIWI 2 PADANG - Irawati, Netti - (Bimbingan dan Konseling, 2014)
This research based by marks sense indisciplinary educative participant to regulation and school discipline. This research is attributed to describe effort any kind that did by counselor to increase participant discipline is taught at SMA Pertiwi 2 Padang with which the focus of research is effort learns BK increases participant discipline be taught through individual counseling service in: 1) Program structures, 2) Program performing, 3) Evaluation program perform. This research did by qualitative approach which descriptive character is to figure the phenomena, fact and reality whatever available in the field. The technique to collect data will be used is interview, the technique will be used in data process with data reduction, display data and verifikasy. The result of research express to effort BKâs teacher increases students participant disciplines through individual counseling service in: 1) Collation the program with the environmentally adverse assess because BKâs room so little and hot and the need assessment or students participant problem is students participants offend school regulation like come late to the school, 2) Program perform to be seen of base service which is time management, responseâs service passes through to service information, works to equal party concerning and individuals planning pass through individual counseling, 3) Perform of evaluation program with the estimation processes with establish commitment and result estimation immediate.